The Important of the Community of Practice (CoP) in Improving the Primary School Teachers’ Performance in Riau Province - Neni Hermita; Tommy Tanu Wijaya; Naila Fauza; Eva Astuti Mulyani; Jesi Alexander Alim; Riki Apriyandi Putra (Universitas Muhammadiyah Purwokerto, 2021)
Efforts to developing the quality of education is empowering educators. Positive activities that accommodate teachers to improve the quality of education are the activities of the Community of Practice (CoP). Community of Practice (CoP) or KKG in Indonesia Context is a forum for professional development for primary school teachers, and one of which is improving teacher performance. The effectiveness of the CoP really needs to be studied in depth. Therefore, a study was conducted on the role of CoP in improving the performance of primary school teachers in Riau Province. The method is a quantitative descriptive study, which describes the role of CoP activities in improving teacher performance in Riau through quantitative data. The research was carried out in May-August 2020. The participant was elementary schools’ teachers in Riau Province. The data source is the primary school teachers totalling 60 people. Data collection techniques using a questionnaire. Based on the results and discussion, it can be concluded that there are several roles of CoP activities in improving teacher performance, among others: through CoP teachers can discuss in construct learning tools, teachers were able to arrange lesson plans for active learning based on analysis of student needs, learning materials are arranged based on various learning sources, using media active learning, analysing evaluation test and conducting assessments according to active learning and student abilities.